Implementation of the Literacy Movement in Shaping Student Character in Elementary School - Eva Marleni; Sofyan Mustoip; Sulkhah Sulkhah (Jurnal IAI Bunga Bangsa Cirebon, 2024)
A study has been conducted to evaluate the application of the Literacy Movement in shaping the character of students at MI Al Huda, Cirebon Regency. The focus of this research is on programs such as Qiraati, readlah, Tahfidz, and literacy zones. The purpose of this research is to understand the character education applied at MI Al Huda. The character applied can encourage all students to show empathy, care, and respect for each other. So character education is an activity that is carried out consciously and helps students know good things, have noble character, are full of affection, and are intelligent. The Literacy Movement in Schools is a social initiative that involves cooperation from various sectors. One way to achieve this is to create a reading habit in students for 15 minutes. The achievement targets of the literacy movement in schools can gradually improve skills achieved through appropriate activities in elementary schools that emphasize reading, listening, and writing skills. This study uses a qualitative method by collecting data through observation, interviews, and documentation. The results show that the Literacy Movement, especially through the Literacy Movement program, is considered effective and receives support from the local community because being interested in these programs can help shape the positive character of students. The implementation of the Literacy Movement to shape the character of grade II students at MI Al Huda, Cirebon Regency has proven to be effective. Through this literacy program, students can develop a disciplined, responsible, independent, intelligent, and capable of respecting others, loving virtue, maintaining honesty, being polite, obeying rules, and obeying religious teachings. This research is expected to provide valuable information and input for the learning process in various institutions or schools, especially at MI Al Huda Cirebon Regency.